Administrative penalty proceedings in the light of the proposed changes to the Fiscal Penal Code (Ius Novum, 2023)
This study discusses the assumptions of the draft act of April 13, 2022 amending the Act – Fiscal Penal Code and some other acts in the scope of administrative penalty ticket proceedings conducted in cases of fiscal petty offences. The main stream of considerations is the presentation of the proposed changes (finally withdrawn) regarding the extension of the catalogue of bodies authorized to conduct administrative penalty proceedings to include the Municipal Police and the Trade Inspection Authority, and to define their competence. In addition, the article contains a presentation of the positions that were submitted by entities as part of public consultations on the draft in question. The publication ends with conclusions in which the author evaluates the currently applicable legal regulations regarding the title issue.
Keywords: administrative penalty proceedings; fiscal petty offences; Municipal Police; Trade Inspection Authority